A comparison of gas temperatures measured by ultraviolet laser scattering in atmospheric plasma sources. (3rd November 2015) - Sommers, Bradley S; Adams, Steven F
Abstract: A laser scattering system utilizing an ultraviolet laser with a triple grating spectrometer has been assembled in order to measure gas temperature in atmospheric plasma sources. Such laser scattering interactions offer a non-invasive technique for investigating atmospheric microplasma sources, which have potential applications in remote optical sensing, materials processing, and environmental decontamination. This particular system is unique in that it utilizes a ultraviolet laser line (266 nm), which increases the cross section for Rayleigh and Raman scattering by a factor of 16 in comparison to the more common 532 nm laser operating in the visible range. In this work, the laser scattering system is used to directly compare the rotational gas temperature ( T r ) and gas kinetic temperature ( T g ) in two different atmospheric plasma sources [001 ]: a direct current plasma jet operating on nitrogen and [002 ] a conventional pin–pin glow microdischarge in air. Results show agreement between T r and T g both in the low temperature afterglow of the plasma jet (300–700 K) and the hot center of the atmospheric glow (1500–2000 K). These observations lend credence to the common assumption of rotational relaxation in atmospheric plasmas and validate the ultraviolet laser diagnostic for future application in atmospheric microplasma sources.